If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3 + -1c) = 5c + 3 (3 * 5 + -1c * 5) = 5c + 3 (15 + -5c) = 5c + 3 Reorder the terms: 15 + -5c = 3 + 5c Solving 15 + -5c = 3 + 5c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5c' to each side of the equation. 15 + -5c + -5c = 3 + 5c + -5c Combine like terms: -5c + -5c = -10c 15 + -10c = 3 + 5c + -5c Combine like terms: 5c + -5c = 0 15 + -10c = 3 + 0 15 + -10c = 3 Add '-15' to each side of the equation. 15 + -15 + -10c = 3 + -15 Combine like terms: 15 + -15 = 0 0 + -10c = 3 + -15 -10c = 3 + -15 Combine like terms: 3 + -15 = -12 -10c = -12 Divide each side by '-10'. c = 1.2 Simplifying c = 1.2
| (4/x)=(2/3) | | x-1/3-x=0 | | 5+5x=-7x | | 6a-2=7 | | x-1/3-× | | 0(4/x)(2/3) | | 4(2l+10)=88 | | 100y-y-10=0 | | 3(a-3)=60 | | x^2-21x+17=0 | | 5x+3=13+e | | x-9=79 | | x-19=299 | | 10f+8=33 | | 8s^2-2s-7s=0 | | 27-x=29 | | x-71=100 | | a/2.5=13/10 | | (q-3)*3=24 | | x-8=48 | | x+5=44 | | x-2=40 | | x+4=356 | | X/5=2/5 | | x-32=199 | | W/3=2/5 | | (x/3-2)(3/4x-24)=0 | | 6+7(6g)-5= | | x+24=200 | | x+13=56 | | 60+60*1+1=61 | | (D^4-2D^2+1)y=0 |